INVESTMENT FEASIBILITY STUDY OF PT HARDAYA MINING ENERGY SEBAKIS ON SITE COAL LABORATORY IN 2022 - ken ken; Febrianto Febrianto; Ali Ridho (Jurnal Ilmiah Global Education, 2023)
PT Hardaya Mining Energy (PT HME) as a coal supplier in Indonesia with a quantity of 3 million Metric Tons (MT) per year is still testing coal samples by sending a large number of samples per day to PT Sucofindo Tarakan Branch and also other PT Sucofindo Branches in the Kalimantan region which costs a lot of additional shipping costs and makes the certificate issuance time long,  so PT HME plans to work with PT Sucofindo Tarakan Branch to procure PT HME On Site coal laboratory. The purpose of this study is to assess the financial feasibility of PT HME's On Site laboratory procurement investment. Quantitative descriptive research method is used in this research to find the amount of investment feasibility value based on the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Ratio (PP), and Break Event Point (BEP) formulas. The results of this study show an NPV value greater than zero, the IRR value is at a percentage of 55%, PP produces a value of 0.81 years or 9.76 months, and has a BEP value that increases every year. Thus, PT HME's on-site coal laboratory investment is feasible.